Gerakan Revitalisme Pasca Mustafa Kemal (STUDIA: JURNAL HASIL PENELITIAN MAHASISWA, 2019)
MustafaKemalisthefatheroftheTurkishnation.HewasoncepresidentinTurkey.Hisbackgroundismilitary.Whenbecomingpresident,theideologyusedissecularism.AndwesterncultureisareferenceinTurkey.WhereasIslamiccultureisignore.Afterhedied,Turkeyexperiencearesurrection.Especiallyinthefield ofIslamic education.This Islamic awakening movement.ThismovementrestoresIslamicculturethatwasoncelostfrom theTurkishpeople.